Hindsight bias and the practice of arrests in Poland - Janusz-Pohl, Barbara; Wawrzyńczak, Michał (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
This comparative study deals with the various forms of arrest in the Polish criminal law system. The authors used the dogmatic-legal and comparative methods, and applied the empirical method in several case studies. The background of the considerations is the proposal of a typology of procedural arrests, based on the Code of Criminal Procedure and non-procedural arrests, based on special laws. The main subject of consideration is the risk of instrumentalization of arrest, which can be considered at several levels: structural, concerning the abuse of the grounds for arrest, and peri-arrest activities (such as informing and questioning the detained person). Within these are three risks of instrumentalization: abuse of the law sensu stricto, sensu largo, and violation of law. Hindsight bias helps to understand the risk of the instrumental application of the law. If the law poses a severe risk of instrumentalization, it must be changed. The authors conclude that the Polish legislator ignores these risks until the law is misapplied. Instead, a proper diagnosis of risks should lead to legislative amendments. The authors propose that mandatory recordings of actions should be introduced. To further strengthen the right to defence, the authors propose changes to the sequence of actions (peri-arrest activities), especially regarding the hearing of the arrested person. Moreover, there is doubt about the standards for applying non-procedural arrests, where the general rules of the Code of Criminal Procedure should apply. Still, the diverse status of the bodies authorized to carry out such actions is a factor that increases the risk of instrumentalization.